2020
DOI: 10.1016/j.sjbs.2020.09.044
|View full text |Cite
|
Sign up to set email alerts
|

Role of bone marrow derived-mesenchymal stem cells against gastric ulceration: Histological, immunohistochemical and ultrastructural study

Abstract: The current study aimed to assess the antiulcerogenic impact of mesenchymal bone marrow stem cells (BMMSCs) against gastric ulcer induced by the use of piroxicam in rats and to compare this effect with the antiulcer drug “Pantoloc ®” proton pump inhibitors. The study included histological, histochemical, immunohistochemical and ultrastructural examination in stomach of rats in different study groups. In the ulcerated group, the glandular region of the stomach displayed clear mucosal lesions occurring as perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 35 publications
5
10
0
Order By: Relevance
“…Our work showed a signi cant decrease in the polysaccharides secretion for the ulcer-model rats compared with the other groups (Antodine, pomegranate, and control). This result is in agreement with Alazzouni et al (2020), who reported a noticeable decrease in the mucus polysaccharides distribution at the mucosal lining of rats due to the treatment with a single oral dose of Brexin as NSAIDs drug. Also, this nding agrees with the results by Mahmoud andAbd El-Ghffar (2019).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our work showed a signi cant decrease in the polysaccharides secretion for the ulcer-model rats compared with the other groups (Antodine, pomegranate, and control). This result is in agreement with Alazzouni et al (2020), who reported a noticeable decrease in the mucus polysaccharides distribution at the mucosal lining of rats due to the treatment with a single oral dose of Brexin as NSAIDs drug. Also, this nding agrees with the results by Mahmoud andAbd El-Ghffar (2019).…”
Section: Discussionsupporting
confidence: 93%
“…Our electron microscopic results for the ulcer-model group rats showed that Brexin caused several ultrastructural changes in the mucous cell organelles, including an irregularity in the nucleus membrane, mitochondria degeneration, and vacuolated zymogenic secretory granules. These results are in agreement with Alazzouni et al (2020), who demonstrated that a single oral dose of Brexin in rats caused degeneration in surface mucous cells with an irregular pyknotic nucleus, fragmented rER, and mitochondria. Also, our results are in agreement with Halter et al (2001), who demonstrated that treatment with aspirin in humans caused gastro mucosal damage, which resulted in a severe intramucosal petechial hemorrhage and erosions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The expression of COX-2 was up-regulated in the indomethacin-treated mice, but down-regulated in the EGb 761-treated and pre-treated groups. This strong immunoreactivity to COX-2 in the ulcer model group was consistent with other studies [ 78 , 79 ]. EGb 761 therapy was found to suppress COX-2 expression in several studies, which were linked to its anti-inflammatory activity [ 80 , 81 , 82 ].…”
Section: Discussionsupporting
confidence: 92%
“…In a study by Alazzouni et al, the anti-inflammatory effect of bone marrow mesenchymal stem cells (BM-MSCs) on piroxicam-induced gastric ulcers in rats was compared with anti-inflammatory drugs such as Pantoloc, which is a proton pump inhibitor. This study showed that BM-MSCs have a therapeutic capacity as anti-ulcers due to high antioxidant activity [ 98 ]. In another research, ADMSCs were used in aspirin-induced gastric ulcers.…”
Section: Introductionmentioning
confidence: 99%